Pendampingan Terjemah Perkata pada Komunitas Translator di Ponpes Bustanul Ma’arif Jember - Ahmad Mizan Rosyadi Abdul Jalil Mannan; Mahmud Mau Robbi (INAIFAS Press, 2022)
Translating the Qur'an is the first step to understanding its contents. As an effort to get inside the Qur'an, the translator community needs intensive assistance through word translation for beginners. The purpose of this service was to provide assistance to the translator community at Ponpes Bustanul Ma'arif Jember in learning translation with PPTQ with a community development approach. Changes that occurred after mentoring the translator community were motivated to explain Qur'an, and they were easy to memorize vocabulary. Translating words with PPTQ has attracted the attention of the community to be more active in studying and understanding words. Learning to translate words with PPTQ can be used as a creative development of the community in the field of Arabic translation.